Abandoned, lost or otherwise discarded fishing gear (ALDFG) in Sri Lanka – A pilot study collecting baseline data. (February 2023) - Gallagher, Anthony; Randall, Peter; Sivyer, David; Binetti, Umberto; Lokuge, Gayathri; Munas, Mohamed
Abstract: Despite increasing attention globally, there has been only limited data collected on the extent of abandoned, lost and otherwise discarded fishing gear (ALDFG) globally. This pilot study was conducted using a fisherfolk survey to quantify the scale of the problem and identify contributory factors in Sri Lanka. Funded through the Ocean Country Partnership Programme (OCPP), and delivered under the Blue Planet Fund, the survey took place in February and March 2022, and involved sampling 325 vessels categorised by vessel type and gear. Based on this survey, 22, 593 kg plastic fishing gear was estimated to have been 'lost' to the marine environment over the previous year. This averages 116 kg per vessel from those vessels that admitted ALDFG events and provides an indication of the scale of ALDFG from the Sri Lankan fishing industry. The survey identified ALDFG drivers, including oceanic and meteorological conditions; a lack of education and awareness amongst fishers; and poor waste management facilities both onboard and onshore. The significance of the drivers varied spatially. Gear conflict was universal though the interaction between Sri Lankan fishers and Indian bottom trawlers in the north was highlighted as was the interaction between fishers and the international shipping lane in the south and west. Changes in national and international policy, as well as more direct national engagement with the issue are recommended, including training, capacity building and the development of better waste infrastructure. Further evidence is required to explore gear conflict and the interaction between ALDFG and international shipping.